Pemijahan dan Perkembangan Embrio Ikan Pelangi, Melanotaenia spp. Asal Papua - Chumaidi, Chumaidi; Nur, Bastiar; Sudarto, Sudarto; Pouyaud, Laurent; Slembrouck, Jacques (Universitas Gadjah Mada, 2009)
Rainbow fish (Melanoptaenia spp.) originated from Sungai Gelap of Papua. The objective of this experiment was to know the fecundity, hatching rate and the rate of embryogenesis. Total of 50 male and female broodstock measuring 10–15 cm reared in closed recirculating water system in concrete tank until their gonad matured. One pair composed of one male and two female’s of matured fish was transferred to 1 x 1 x 0.5 m³ concrete tank for pair breeding, the fish was sheltered with water hyacinth. Released eggs were observed in the morning and in the afternoon daily. Eggs were categorized into fertile and infertile. Some 25 eggs were incubated in plastic baskets, and observed under microscope for their embryonic development stages. The results showed that rainbow fish from Sungai Gelap produced eggs (averages) 392 per female; fertility rate was 93.74%; average hatching rate was 87.36%, and the fertilized eggs were hatched approximately 5 days incubation.